Divertor currents during type-I edge-localized modes on the DIII-D tokamak. (11th October 2019) - Knolker, M.; Evans, T.E.; Wingen, A.; Bortolon, A.; Laggner, F.M.; Moyer, R.A.; Nazikian, R.; Zohm, H.
Abstract: Measurements of divertor currents on DIII-D lead to new insights in nonlinear edge-localized mode (ELM) dynamics and a possible mechanism to explain their explosive growth. Rapidly oscillating currents flowing into the divertor before a significant increase in divertor heat flux occurs are measured with an array of shunted tiles and characterized. Extrapolation results in total n = 0 currents of 5–10 kA flowing into a concentric circle near the strike point. The detected Fourier harmonics appear consistent with a mix of low- n modes ( n < 4) with currents up to 4 kA. A heuristic framework for ELM currents is developed based on thermoelectric origin of the tile currents with flow through regions inside of the nominal separatrix and found consistent with the current measurements. A current flow through the confined plasma leading to increased stochasticity and transport at the plasma edge could provide a mechanism for additional nonlinear growth as sought for in computational ELM simulations. Results also imply that ELM currents may open the possibility to manipulate the ELM character by perturbations through non-axisymmetric divertor bias or tile insulation.